Importance of Prevention and Early Intervention of Adverse Events in Pediatric Cardiac Catheterization: A Review of Three Years of Experience - Yu-Chih Huang; Jeng-Sheng Chang; Yung-Chang Lai; Ping-Chun Li (Elsevier, 2009)
In spite of advances in many noninvasive instruments for studying cardiac anomalies in children, cardiac catheterization (CC) is still an essential method for the precise calculation of cardiovascular hemodynamic status and for performing therapeutic interventions. Accordingly, all adverse events (AE) related to CC are a major concern to pediatric cardiologists. Patients and Methods: A total of 220 children with congenital heart disease (CHD) who received cardiac catheterization in our tertiary care hospital between the period of January 2000 and December 2002 were studied. One hundred and thirty-eight patients were non-cyanotic CHD, 71 were cyanotic CHD and 11 were complex CHD. Diagnostic CC was performed in 138 patients and therapeutic CC in 82 patients. All AEs that occurred during the CC procedures were identified, recorded and managed at the scene. The severities of AE were further classified into minor, obvious and severe. Results: AEs were observed in 41 patients, including 22 (10%) minor, 16 (7.27%) obvious and 3 (1.36%) severe AEs. The three severe AEs were cardiac tamponade, severe ventricular tachycardia and marked hypoxia-and-bradycardia. None of the patients died. Therapeutic CC did not present a higher incidence of AE occurrence than diagnostic CC. However, a young age (p< 0.0001), low body weight (p< 0.0001) and cyanotic or complex CHD (p= 0.01) appeared to be risk factors for obvious and severe AE. Conclusion: Although the complication of severe AE during CC may not be totally preventable, it is important to be aware of every early sign of AE and to initiate an effective intervention by a well trained resuscitation team.